Influence of Cryptocurrency and Intellectual Capital on Share Value of Financial Sector Companies Listed on the Indonesia Stock Exchange 2017-2021 - Pramana, Andhika Yuda; Karnowahadi, Karnowahadi -; Salsiyah, Sri Marhaeni (Politeknik Negeri Semarang, 2023)
This research aims to analyze the influence of cryptocurrency (X1) and intellectual capital (X2) on stock value (Y) of Monetary Sectors Company In Bursa Efek Indonesia 2017-2021. The data collection method used in this research were documentation and literature study. The sample collecting method used was non probability sampling on 46 monetary companies in Bursa Efek Indonesia 2017-2021. The data analysis method used were classic assumption test, multiple linear regression, F test, the coefficient determination, and t test. Based on calculations using software IBM SPSS 25 version, the result of this research showed that the regression equation Y=6,959+0,013X1+0,139X2. In addition, the F test result showed significant of 0,000 lower than 0,05. The t test result of cryptocurrency has sig more than 0,05. So, it can be concluded the cryptocurrency (X1) have an influence but not significance on stock value (Y) of Monetary Sectors Company In Bursa Efek Indonesia 2017-2021 and intellectual capital (X2) had a significance influence on stock value (Y) of Monetary Sectors Company In Bursa Efek Indonesia 2017-2021. The most influential variable is intellectual capital (X2) with the highest regression coefficient of 0,139.